(untitled) (Journal of research in medical and health sciences, 2026)
Against the backdrop of the popularization and digital transformation of higher education, the economic pressure and psychological development needs faced by the impoverished student group in colleges and universities are intertwined, becoming an important issue affecting educational equity and the quality of talent cultivation. Reading therapy, as an economical, safe and profoundly influential psychological aid, is increasingly highlighting its value. However, a single university library has limitations in terms of resource reserves and professional service capabilities, making it difficult to implement large-scale, personalized and continuous reading intervention for impoverished students. This research takes "sharing, precision and empowerment" as its core concepts, aiming to explore how to rely on the inter-library mutual assistance mechanism of digital and intelligent libraries in universities within the province to build a systematic, collaborative and intelligent reading therapy support system for impoverished students in universities. The article first analyzes the current situation and predicament of reading therapy services carried out by university libraries at present, especially those for students from poor families. Secondly, it expounds the necessity and feasibility of combining digital intelligence technology with inter-library mutual assistance. Furthermore, from four dimensions: the resource layer, the platform layer, the service layer, and the mechanism layer, the theoretical model and implementation framework of this support system were constructed in detail, and a closed-loop service process including precise demand identification, intelligent resource matching, dynamic process intervention, and scientific effect evaluation was designed. Finally, the guarantee strategies and future prospects for the implementation of the system were proposed, with the aim of providing theoretical references and practical paths for promoting educational equity, enhancing the accuracy and effectiveness of psychological education in colleges and universities, and driving the intelligent transformation and service innovation of libraries. This study contains an explanatory table on the "core components and functions of the support system".